2015
DOI: 10.1007/s12016-015-8516-5
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History and Prognosis of Primary Biliary Cirrhosis with Clinical Features of Autoimmune Hepatitis

Abstract: Although a variant of primary biliary cirrhosis (PBC) characterized by features of autoimmune hepatitis (AIH) has been recognized for many years, few studies with ample numbers of patients have focused on its natural history. This study aimed to clarify the natural history, prognosis, and response to therapy in a cohort of patients with PBC with AIH features. We retrospectively analyzed 277 PBC patients without AIH features and 46 PBC patients with AIH features seen between September 2004 and April 2014. The 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 45 publications
5
44
0
Order By: Relevance
“…for the first time proposed the underestimated male prevalence of PBC 15 , followed by 2 geoepidemiology researches in the West, where the female: male ratio could decrease to 1.6:1 from administrative databases in Sweden 5, 6 . The gender ratio in our study also corroborated the results of recent studies from South Korea and Japan (6.2:1 and 7.0:1, respectively) 16, 17 and is much lower than those in previous reports from China 9, 10 . This study is the largest of Chinese PBC patients and implies that the evolving trend of female to male incidence in China is similar to that observed in Western populations 5, 6 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…for the first time proposed the underestimated male prevalence of PBC 15 , followed by 2 geoepidemiology researches in the West, where the female: male ratio could decrease to 1.6:1 from administrative databases in Sweden 5, 6 . The gender ratio in our study also corroborated the results of recent studies from South Korea and Japan (6.2:1 and 7.0:1, respectively) 16, 17 and is much lower than those in previous reports from China 9, 10 . This study is the largest of Chinese PBC patients and implies that the evolving trend of female to male incidence in China is similar to that observed in Western populations 5, 6 .…”
Section: Discussionsupporting
confidence: 92%
“…The disease spectrum often differs between the East and West (e.g., with regard to hepatitis B, hepatitis C, and autoimmune hepatitis; AIH). Recently, several studies have explored the clinicopathological characteristics of patients with PBC in China, and two reports found that the female:male ratio was 11.6:1 and 10.9:1, respectively 9, 10 . However, these studies in China have been performed in developed areas, such as Shanghai and Beijing, rather than developing areas.…”
Section: Introductionmentioning
confidence: 99%
“…Second‐line immunosuppressants (cyclosporine A, tacrolimus and MMF) induced biochemical remission in 54% of patients who did not respond to initial immunosuppressive agents. A recent study in China showed that a combination therapy of glucocorticoid and UDCA could significantly improve the short‐term prognosis of patients with overlap syndrome …”
Section: Treatment For Aih Of Special Clinical Phenotypesmentioning
confidence: 99%
“…Combination treatment with budesonide and UDCA was more efficacious than UDCA monotherapy for PBC/AIH overlap syndrome[159]. Furthermore, combination treatment with immunosuppression and UDCA offered better short-term responses in PBC/AIH overlap syndromes[160]. …”
Section: Differential Diagnosis Of Pbcmentioning
confidence: 99%
“…Furthermore, the pooled 2 year rates of death, transplant, and progression of varicosities were 11.4%, 8.7% and 10.6%, respectively, in patients treated with placebo[165]. The natural history of PBC patients with AIH characteristics significantly differs from those without AIH characteristics[160]. In addition, although considered to possess a higher prevalence rate of AMAs, first-degree relatives of PBC patients have a lower risk of developing PBC over time, especially in those without baseline biochemical test evidence of intrahepatic cholestasis[166].…”
Section: Natural History Of Pbcmentioning
confidence: 99%